The relevance of the doctrine of collation in the modern-day South African law of succession - Weldman, Julian (Department of Public Law, 2026)
The practice of transferring inter vivos gifts and advances from parents to their children is deeply embedded in societal behaviour. This practice plays a significant role in modern family dynamics, often reinforcing the bond and commitment between parents and their children. Parents frequently provide non-reciprocal support to their children for various reasons, including celebrating milestone events, enhancing living conditions, assisting during financial difficulties, or following cultural traditions. However, despite these societal norms, the doctrine of collation in the Law of Succession mandates that a descendant heir who has received an inter vivos gift or advance from their parent must account for specific advances when they accept an inheritance. This doctrine appears to have held more weight during the Roman-Dutch era, when the norms surrounding gift-giving and advances differed from today's perspectives. Thus, it is crucial to reassess the relevance of this doctrine in the present context. It is essential to highlight that the doctrine of collation remains a relatively unexplored area of law, characterised by limited academic discourse and a scarcity of recent case law. This thesis investigates the relevance of the doctrine of collation in contemporary South African society, assessing its compatibility with essential legal principles of the Law of Succession and certain constitutional values. To achieve these aims, I undertook quantitative empirical research to understand public attitudes toward gift-giving and advances and perspectives on the doctrine's significance and implementation. I also engaged in qualitative empirical research and explored how attorneys view collation and the guidance offered to testators in will drafting. This analysis also helped to hypothesise the likely intentions of a deceased person when dying intestate, as the doctrine pertains to both testate and intestate succession. Furthermore, through desktop research, this thesis evaluates how the doctrine of collation aligns with constitutional rights, such as freedom of testation and property rights. Finally, I conducted a comparative analysis of how the doctrine is addressed in Australia. Through my analysis, I have established that the justification for collation, namely, that a deceased intends to treat his or her descendants equally, requires re-evaluation and that the doctrine encroaches upon the constitutionally recognised rights to freedom of testation and property. I also show that the common law categories of advances subject to collation are irrational if the purpose is to establish equality between descendants. Less complicated methods have emerged to achieve the desired outcome of equality. Moreover, the testator's assumption of equal treatment of children is flawed, as parents tend to treat their children differently and do not seem perturbed by this. My comparative analysis reveals that in the face of practical problems associated with collation, the doctrine could be abolished or reformed by taking a more pragmatic approach in Australia. Ultimately, the thesis concludes by suggesting possible law reform initiatives to the common law of collation but cautions against the abolishment of the doctrine without further investigation by the South African Law Reform Commission